Pythagorean fuzzy TODIM approach to multi-criteria decision making - Ren, Peijia; Xu, Zeshui; Gou, Xunjie (Applied soft computing, 2016)
•Develop the Pythagorean fuzzy TODIM approach to multi-criteria decision making.•The developed approach can portray the uncertainty and risk simultaneously.•Conduct the simulation tests to verify risk attitude's influence on the ranking orders.•Provide a case study to show the practicality and effectiveness of the proposed approach.•Demonstrate the superiority of our approach by comparing it with the existing ones. Recently, the TODIM (an acronym in Portuguese for Interactive Multi-criteria Decision Making) approach, which can characterize the decision makers’ psychological behaviours under risk, has been introduced to handle multi-criteria decision making (MCDM) problems. Moreover, Pythagorean fuzzy set is an effective tool for depicting uncertainty of the MCDM problems. In this paper, based on the prospect theory, we first extend the TODIM approach to solve the MCDM problems with Pythagorean fuzzy information. Then, we conduct simulation tests to analyze how the risk attitudes of the decision makers exert the influence on the results of MCDM under uncertainty. Finally, a case study on selecting the governor of Asian Infrastructure Investment Bank is made to show the applicability of the proposed approach.